THE CONCEPT OF HYPOCRISY IN THE QURAN AND ITS COMPARISON WITH CARL GUSTAV JUNG'S THEORY OF PERSONA - Hidayatulloh, Muhammad Mahbub; Soleh, Achmad Khudori; Cholili, Abd Hamid (LP2M IAI Al-Khairat Pamekasan, 2025)
This study examines the concept of hypocrisy (nifaq) in the Qur’an and compares it with Carl Gustav Jung’s theory of persona in analytical psychology. The main objective is to identify the similarities and differences between hypocrisy as a moral–spiritual phenomenon and persona as an adaptive psychological mechanism. Employing a qualitative approach through library research and comparative textual analysis, this study draws on primary sources such as the Qur’an, classical and modern exegeses, and Jung’s works. The findings reveal that both nifaq and persona describe a dissonance between one’s inner and outer selves. However, they differ fundamentally in nature: nifaq in the Qur’an is morally destructive, rooted in deceit and ill intent, whereas persona in Jung’s framework is adaptive, becoming harmful only when the individual loses authenticity. The study underscores the importance of honesty, self-reflection, and the integration of spiritual and social identities in developing authentic human character in the modern era.